RESURGENCE OF RUSSIA AS A GREAT POWER AND ITS FOREIGN POLICY ORIENTATION TOWARDS SOUTH ASIA (Margalla Papers, 2020)
Russia has re-emerged as an important global actor after the advent of the post-Soviet era. Kremlin’s repositioning in the global affairs under President Vladimir Putin has led to a geopolitical and geostrategic transformation of its foreign policy. It follows multilateralism with active outreach in different parts of the world. In contemporary Russian foreign policy, there are tangible determinants that call for multipolar world order including realignment of foreign relations and consolidation of great power status. This paper, therefore, examines Russian foreign policy in the post-Crimean annexation era, where Moscow launched various campaigns through active engagements with the world’s larger economies and strategically important countries, such as China, India, Pakistan, and Afghanistan. The paper also highlights Russia’s evolving bilateral relations with these countries, especially in economic, political, and military spheres. Following the current global geopolitical realities, it also attempts to mark clear adjustments in Moscow’s foreign policy with respect to its power, responsibility, and ambitions for international peace and stability. Bibliography EntryShah, Syed Taimoor, and Ayesha Afgun. 2020. "Resurgence of Russia as a Great Power and Its Foreign Policy Orientation towards South Asia." Margalla Papers 24 (2): 93-103.